Mechanisms in sociology—a critical intervention - Döllinger, Dominik (Frontiers in Sociology, 2024)
The notion of the mechanism is one of the most popular and widely used concepts in science and sociology is no exception. This paper problematizes the widespread and often uncritical use of the term “mechanism” in contemporary sociology. Drawing on the mechanistic worldview associated with leading figures of the scientific revolution, the paper emphasizes the impact of mechanistic thinking on the societal rationalization process identified by Max Weber and the Frankfurt School. The analysis suggests that mechanisms, when applied to sociological theories, may uncritically reproduce a cultural fetish of the rational society with potentially dehumanizing consequences. The author advocates for a critical reflection on the cultural and historical context of mechanisms, urging sociologists to view them not merely as analytical tools but as active contributors to the creation and shaping of social worlds erected on a belief in instrumental reason.